Pertumbuhan Bibit Karet (Hevea brasiliensis) Stum Mata Tidur Dengan Pemberian Air Kelapa dan Ampas Teh - Mei Simtalia; Armaini '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The aimed of this research was to know the influence of coconut water and tea dregs on the growth stum sleep eyes, look at the concentration of coconut water and tea dregs dose and the best combination for the growth of the eye stum rubber bed. The research was done experimentally by using Completely Randomized Design (CRD) by using two factors: the first factor is the provision of coconut water A1 = 250 cc/ l, A2 = 500 cc/ l, A3 = 750 cc/ l. The second factor is the provision of tea waste B1 = 80 g/ polybag, B2 = 100 g/ polybag, B3 = 120 g/ polybag. Data were analyzed statistically using Analysis Of Variance (ANOVA) followed by a further test DNMRT at 5% level. Parameters measured were time buds appear (days), shoot length (cm), number of leaves (pieces), shoot diameter (cm), shoot dry weight (g). Combination treatment with coconut water giving 750 cc/ l with the dregs of tea 120 g/ polybag showed the best results for the time parameter appearing shoots, shoot length, number of leaves, stem diameter and dry weight of shoots. Keywords : stum sleep eyes, coconut water, tea dregs